Algorithmic Colonialism: Artificial Intelligence and the New Structure of Global Power - Gama Santos, Jose; Utrera, Fiorella (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
The rapid development of artificial intelligence (AI) has transformed the contemporary structure of global power by shifting domination from territorial control toward computational and algorithmic control. This study examines the concept of algorithmic colonialism as a new form of global inequality operating through data extraction, digital infrastructures, and technological dependency. Using a qualitative and conceptual approach, the research analyzes the relationship between AI, surveillance capitalism, platform governance, and geopolitical competition within the framework of postcolonial theory and critical political economy. The findings demonstrate that AI technologies are not politically neutral but function as mechanisms of economic, political, and cultural domination. Multinational technology corporations and technologically advanced states increasingly control global data flows, communication infrastructures, and computational systems, thereby creating asymmetrical dependencies between technologically dominant and digitally dependent societies. The study also reveals that algorithmic systems contribute to surveillance practices, democratic fragmentation, epistemological inequality, and the concentration of technological power within a limited number of global actors. Furthermore, the geopolitical competition surrounding AI development intensifies global inequality by reinforcing technological dependency and limiting digital sovereignty in developing countries. This article argues that algorithmic colonialism represents a contemporary continuation of historical colonial logic operating through digital mechanisms rather than physical occupation. The novelty of this study lies in its interdisciplinary integration of postcolonial theory, digital political economy, and AI governance into a unified conceptual framework explaining how artificial intelligence restructures global political authority in the digital era. Ultimately, the study emphasizes that struggles over data ownership, technological sovereignty, and computational governance will become defining political challenges of the twenty-first century.